KETIDAKJELASAN BATAS KERUGIAN DARI TINDAK PIDANA PENGHINAAN - Prahassacitta, Vidya; Candra, Livia Vanessa (Justitia et Pax, 2024)
The research aims to analyze the harm limits of defamation offenses that shall be criminalized. The research analyzes four court decisions. In those court decisions, the defendants are punished with mild punishment (under 1 year imprisonment) using Article 27 (3) Jo. 45 (3) Information and Electronic Transaction Act, and all of victims are ordinary citizen not a public official or public figure. The research is doctrinal legal research using secondary data from literature study. Research result shows it requires a clear danger of speech to criminalize defamation behavior. Harm cannot only be measured with debate and discussion that have become a trending topic in social media, but it also requires a clear danger of the speech against the victim in society. For instance, when society ostracizes the victim, they lose jobs, opportunities, and financial benefits, and they experience mental disorders. Analyzing court decisions shows that most of the judges’ ignorance the impact of the defendant's speech on the victim’s private and social lives. In the end, unclear harm limitations and the seriousness level of harm in a defamation offense create uncertainty in defamation cases.